2016
DOI: 10.1038/srep39290
|View full text |Cite
|
Sign up to set email alerts
|

Sodium selenate regulates the brain ionome in a transgenic mouse model of Alzheimer’s disease

Abstract: Many studies have shown that imbalance of mineral metabolism may play an important role in Alzheimer’s disease (AD) progression. It was recently reported that selenium could reverse memory deficits in AD mouse model. We carried out multi-time-point ionome analysis to investigate the interactions among 15 elements in the brain by using a triple-transgenic mouse model of AD with/without high-dose sodium selenate supplementation. Except selenium, the majority of significantly changed elements showed a reduced lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 81 publications
(100 reference statements)
1
18
0
Order By: Relevance
“…We have already reported that sodium selenate positively alter the expression of various proteins involved in vital functions in hippocampus of transgenic AD mice (Iqbal et al, ). Enhanced Se concentrations and its association with antioxidant protein GPx in 3 × ‐Tg AD mice has already been established by us and (Zheng et al, ) and another study (Reddy et al, ). Here in this study, we have used cortex which is also badly affected by AD and nourished the AD mice with sodium selenate dissolved in water and observed its proteomic expressions as compared to AD and non‐transgenic mice using standard iTRAQ proteomics technology.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We have already reported that sodium selenate positively alter the expression of various proteins involved in vital functions in hippocampus of transgenic AD mice (Iqbal et al, ). Enhanced Se concentrations and its association with antioxidant protein GPx in 3 × ‐Tg AD mice has already been established by us and (Zheng et al, ) and another study (Reddy et al, ). Here in this study, we have used cortex which is also badly affected by AD and nourished the AD mice with sodium selenate dissolved in water and observed its proteomic expressions as compared to AD and non‐transgenic mice using standard iTRAQ proteomics technology.…”
Section: Discussionsupporting
confidence: 60%
“…This data shows that low Se levels in plasma has strong association with cognitive decline. To further confirm this hypothesis, we have measured the Se concentrations in cerebrum of wild type (WT), 3 × Tg‐AD, and Se supplemented 3 × Tg‐AD mice and found low levels of Se in 3 × Tg‐AD mice as compared to WT and Se supplemented 3 × Tg‐AD mice (Zheng et al, ). Some of Se‐containing compounds like selenite, selenate, or selenomethionine were supplemented to the AD animal models and they were found quite effective causing improvements in cognition functions (Corcoran et al, ; Papp, Holmgren, & Khanna, ).…”
Section: Introductionmentioning
confidence: 91%
“…They also analyzed ionomic variations in the mouse brain after a long-term dietary supplementation of Zn. Zheng et al performed a multi-time-point ionomic analysis to investigate the interactions among 15 elements in the brain by using 3xTg-AD mice receiving high-dose sodium selenate dietary supplementation, which revealed that Se intake could significantly reduce the concentrations of a variety of elements in the brain, especially Fe (a known risk factor for AD) whose level was completely reversed to normal state [ 127 ]. In addition, by building the elemental correlation network, significant and time-specific elemental correlations and correlation changes were identified.…”
Section: Ionomics Of Complex Diseasementioning
confidence: 99%
“…Then, the residue was dissolved in 10 mL of 0.5 M HCl. The Se content was measured by inductively coupled plasma-mass spectrometry (ICP-MS, Perkin-Elmer SCIEX, Norwalk, CT, USA) after digestion based on a calibration curves constructed using a Se standard solution [GBW(E)080215, 100 pg/mL] (National Standard Material Research Center, Beijing, China) (Zheng et al, 2016). The RF power was 1,100 W and the nebulizer used was Meinhard ® .…”
Section: Measurement Of the Se Contentmentioning
confidence: 99%